Selective pharmacological inhibitors of HDAC6 reveal biochemical activity but functional tolerance in cancer models. Issue 3 (20th February 2019) - Depetter, Yves; Geurs, Silke; De Vreese, Rob; Goethals, Sophie; Vandoorn, Elien; Laevens, Alien; Steenbrugge, Jonas; Meyer, Evelyne; de Tullio, Pascal; Bracke, Marc; D'hooghe, Matthias; De Wever, Olivier
Abstract : Our study investigates the biochemical and functional impact of selective histone deacetylase 6 (HDAC6) inhibitors, a promising class of novel therapeutics, in several cancer models. Selective HDAC6 inhibitors (Tubathian A, Tubastatin A, Tubacin and Ricolinostat) and a non‐selective HDAC inhibitor (Vorinostat) were evaluated on cancer cell lines derived from multiple tumour types in both an in vitro and in vivo setting as potential cancer therapeutics. Selective HDAC6 inhibitors resulted in α‐tubulin acetylation with no impact on histone acetylation but failed to show any anti‐cancer properties. Only the use of high concentrations of selective HDAC6 inhibitors resulted in co‐inhibition of other HDAC enzymes and consequently in reduced growth, migratory and/or invasive activity of cancer cells in vitro as well as in vivo . The specificity of HDAC6 inhibition was confirmed using a CRISPR/Cas9 knockout cell line. Our results suggest that selective HDAC6 inhibitors may fall short as potential single agent anti‐cancer drugs and prove that many previous data regarding this promising class of compounds need to be interpreted with great care due to their use in high concentrations resulting in low selectivity and potential off‐target effects. Abstract : What's new? Histone deacetylase 6 (HDAC6) helps regulate cell growth, metastasis, and invasion in tumour cells, making it an appealing target for anti‐cancer therapies. This study shows that in cancer cells, selective HDAC6 inhibitors increase acetylation levels of α‐tubulin, an HDAC6 substrate, without affecting histone acetylation. HDAC6 inhibition, however, did not reduce tumour cell growth or block tumour cell migration or invasion. Moreover, HDAC6 inhibitors exhibited anti‐tumour activity in vitro and in vivo only when administered in high concentrations, which also produced off‐target effects. The findings suggest that further study is needed to clarify data on anti‐cancer effects of selective HDAC6 inhibitors.